2018
DOI: 10.1111/liv.13987
|View full text |Cite
|
Sign up to set email alerts
|

The impact of HCV eradication by direct‐acting antivirals on the transition of precancerous hepatic nodules to HCC: A prospective observational study

Abstract: Background & Aims It remains controversial whether the eradication of hepatitis C virus (HCV) by interferon (IFN)‐free anti‐HCV therapy using direct‐acting antivirals (DAAs) suppresses or promotes hepatocellular carcinoma (HCC) development. We investigated the influence of HCV eradication by DAA therapy on HCC development, by observing changes of non‐hypervascular hypointense nodules (NHHNs) by gadolinium‐ethoxybenzyl‐diethylenetriamine pentaacetic acid‐enhanced magnetic resonance imaging (EOB‐MRI). Methods A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 25 publications
3
32
1
Order By: Relevance
“…Although NHHNs emerged even after SVR in our previous study, 14 it will not emerge in patients whose liver fibrosis was mild before SVR. Given the dramatic increase in the number of HCV patients who achieved SVR in the era of interferon-free DAA therapy, this finding can be used for the stratification of the intensity of HCC surveillance after SVR.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Although NHHNs emerged even after SVR in our previous study, 14 it will not emerge in patients whose liver fibrosis was mild before SVR. Given the dramatic increase in the number of HCV patients who achieved SVR in the era of interferon-free DAA therapy, this finding can be used for the stratification of the intensity of HCC surveillance after SVR.…”
Section: Discussionmentioning
confidence: 53%
“…Our previous study reported that 43.5% of NHHNs became hypervascularised during 12 months of follow‐up . In addition, the eradication of HCV with DAA‐based anti‐HCV therapy did not suppress this hypervascularisation if it existed before HCV eradication . Therefore, it is clinically important to identify patients with NHHNs in the liver, for whom intensive surveillance for HCC should be provided for early HCC detection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LR3/4 nodules are well known as a high‐risk factor of HCC development, and there are suggestions that patients with these nodules should be excluded from analysis. Therefore, subgroup analysis was performed except for patients with LR3/4 nodules.…”
Section: Discussionmentioning
confidence: 99%
“…In WFA + -M2BP and FIB-4, it was impossible to distinguish patients without HCC risk like liver stiffness (data not shown). This was one of the advantages of using liver stiffness for stratification of HCC risk.LR3/4 nodules are well known as a high-risk factor of HCC development,29,30 and there are suggestions that patients with these nodules should be excluded from analysis. Therefore, subgroup analysis was performed except for patients with LR3/4 nodules.…”
mentioning
confidence: 99%